MARRIAGE DURABILITY AND FORMS OF DOMESTIC VIOLENCE IN MANIPUR: CASE STUDY OF A SWADHAR GREH - M. Jimbashwari Devi; Lilee, Ma yanglambam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Marriage is a social institution in which a man and woman unite and start a new beginning of a family. It includes the social sanctity and cultural heritage of a community. Marriage system varied from one community or region to another across the globe, Meitei of Manipur, North-East India have also unique way of social acceptance when it comes to traditional marriage practices. It consists of various rituals, functions, and deep-cultural practices. It is also a tight knot of a beautiful new life journey. However, it sometimes misleads directly or indirectly and traps women in unhealthy conditions of social problems. The notion of a marriage is to live together and forever throughout life. Nevertheless, this preconceived notion of togetherness can misguide women, and they are often the victims of domestic violence. Domestic violence is a violent/potential act of behavior that causes harm/injury to anyone in the form of physical, mental, sexual, or economic abuse and is also a social problem in every society. In Manipur, there is a high rate of spousal domestic violence in the NFHS-5. In this context, the study focuses on the linkages of duration of marriage and different forms of domestic violence in Manipur. Thus, the study explores the secondary sources and the primary data of a Swadhar Greh in Manipur to understand domestic violence as social problem.